Pengaruh profitabilitas, leverage, ukuran perusahaan, dan likuiditas terhadap nilai perusahaan - Wicaksono, Bambang Tri; Fitriati, Ika Rosyada (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
The author of the study aims to examine the factors that affect firm value. There are several variables used, namely profitability, leverage, firm size, and liquidity. The purpose of this research is to find out empirically namely profitability, leverage, firm size, and liquidity affect firm value in the financial sector of companies listed on the Indonesia Stock Exchange for the period 2017-2020. The research sample using purposive sampling method, obtained as many as 33 financial sector companies for 4 years based on certain criteria. The research shows that the profitability variable does not affect firm value, liquidity does not affect firm value, leverage affect but does not significantly affect firm value, and firm size significantly affect firm value.